2017
DOI: 10.1159/000488893
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years After: Another Case Report of Melatonin Effects on REM Sleep Behavior Disorder, Using Serial Dopamine Transporter Imaging

Abstract: Introduction: REM sleep behavior disorder (RBD) is considered a prodromal phase of α-synucleinopathy like Parkinson disease (PD). PD is characterized by a progressive decline of dopamine (DA) in the striatum. Here we report the surprising increase in DA transporter density over successive years in an RBD patient treated with melatonin. Case Presentation: A then 72-year-old man was clinically suspected to suffer from PD in 2011. DA transporter scintigraphy (DaTSCAN) revealed reduced DA transporter density, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…These results challenge the current clinical assumptions on the efficacy of melatonin for RBD, 8,9 although previous studies included small samples with a variety of disorders, questioning their generalizability to PD. [6][7][8][9][11][12][13][14][23][24][25] The effects of prior trials were often mixed, with several participants not responding to FIG. 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results challenge the current clinical assumptions on the efficacy of melatonin for RBD, 8,9 although previous studies included small samples with a variety of disorders, questioning their generalizability to PD. [6][7][8][9][11][12][13][14][23][24][25] The effects of prior trials were often mixed, with several participants not responding to FIG. 2.…”
Section: Discussionmentioning
confidence: 99%
“…The post-observation period assessed whether the effects would persist. 8,11 Ethical approval was obtained from the Human Research Ethics Committees of the University of Sydney and Royal Prince Alfred Hospital, Australia. The trial was prospectively registered (ACTRN12613000648729) with its protocol published online: anzctr.org.au/ACTRN12613000648729.aspx.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, the scan prior to melatonin treatment had clear signs of PD, the scan recorded 2 years later was considered borderline, with absence of any sign of PD 4 years after the first scan. The results were interpreted as a possible neuroprotective role for melatonin in synucleinopathy (205).…”
Section: Clinical Use Of Melatonin In Pdmentioning
confidence: 98%
“…Indeed, the conversion rate to synucleinopathy in clonazepam-treated RBD patients is high (208, 209). Although no comparable data are available yet for melatonin-treated RBD patients, a recent observation by Kunz and Bes deserves to be considered (205). The investigators reported the increase in DA transporter density (as assessed by DA transporter scintigraphy) over successive years in a 72-year-old RBD male patient treated with 2 mg of slow release melatonin daily.…”
Section: Clinical Use Of Melatonin In Pdmentioning
confidence: 99%